Managerial factors and management conflict in venture capital financing in Malaysia - Mohammad, Hisham; Minai, Mohd Sobri; Lucky, Esuh Ossai Igwe (Canadian Center of Science and Education, 2014)
The warm venture cooperation built between venture capitalists and entrepreneurs may still be interrupted by the management's conflicts occurred due to various managerial factors.As a result, this study investigates the management conflict in venture capital investments.A cross-sectional study of questionnaire survey research design was conducted in this respect.Questionnaire data was generated from 35 Malaysian venture capital companies located in Kuala Lumpur and Selangor.The questionnaires were distributed through the mailing procedure.Overall, the findings indicate that the managerial factors significantly influence the management conflict.Further results show that managerial factors which consist of Deal Origination and Screening (DOS), Evaluating Venture Proposal (EVP), Contracting and Deal Structuring (CDS), Monitoring and Post Investment Activities (MPI) and Risk Management (RM) significantly influence the formation of management conflict in venture cooperation. Based on the findings, it is inferred that managerial factors does influence the occurrence of management conflict in venture cooperation.Thus, the study recommends that Malaysian venture capitalists give consideration to the managerial factors in reducing or curbing the possibility of conflict to occur.